Genetic variant rs72613567 of HSD17B13 gene reduces alcohol‐related liver disease risk in Chinese Han population. (3rd August 2020) - Chen, Haizhen; Zhang, Yanfang; Guo, Tongsheng; Yang, Funing; Mao, Yuanli; Li, Liubing; Liu, Chenxi; Gao, Haidi; Jin, Yuting; Che, Yuanyuan; Li, Yongzhe; Huang, Jing
Abstract: Background & Aims: Recently, the variant rs72613567:TA in the 17‐beta‐hydroxysteroid dehydrogenase 13 ( HSD17B13 ) has been associated with reduced levels of ALT and AST and a reduced risk of alcohol‐related liver disease (ALD) in the European population. Therefore, the aim of this study was to investigate the association between the polymorphisms of HSD17B13 and ALD, liver serum markers and patatin‐like phospholipase domain‐containing protein 3 ( PNPLA3 ) p.I148M in the Chinese Han population. Methods: A case‐control study was performed from five centres and included 769 ALD patients and 767 healthy controls. Two SNPs (rs72613567 and rs6834314) in HSD17B13 were genotyped using the Sequenom MassArray system and allele association analysis was performed using PLINK 1.90 software. Results: HSD17B13 rs72613567:TA allele was associated with a reduced risk of ALD by 19% (95% confidence interval [CI]: 0.05‐0.31, P  = .01), uniformly, the G allele in the rs6834314 reduced the risk of ALD by 19% (95% CI: 0.05‐0.31, P  = 8.28 × 10 −3 ). And the genotypes of two SNPs were associated with reducing the risk of ALD in three genetic model analysis. In addition, we found that TA allele was associated with lower levels of serum ALT, AST and GGT ( P  = .005, .007 and .02, respectively), higher level of serum ALB ( P  = .02), but not associated with ALP. In this cohort, the interaction between HSD17B13 rs72613567 and the steatogenic allele PNPLA3 rs738409 was not validated. Conclusion: The present study revealed that HSD17B13 rs72613567 was significantly associated with a reduced risk of ALD in Chinese Han population.